ONLINE-BASED PROMOTION MODEL IN RECRUITING OUTSTANDING NEW STUDENTS - Wahyudi, Kacung; Badrus Soleh (re-JIEM (Research Journal of Islamic Education Management), 2023)
In this very competitive era of globalization, marketing is likened to the heartbeat for the continuity of educational institutions engaged in services. Promotion is one of the important activities that must be carried out by an institution to maintain its survival in order to develop and achieve the expected goals. The results of this study indicate that: First, the initial design of the promotion model in the form of advertising in the selection of new high achieving students online at MAN 2 Pamekasan started with a meeting to form a committee appointed to prepare everything in implementation. Second, the implementation of online promotional advertising features that are carried out in the selection of new outstanding students based on online using website media and WhatsApp in the registration process. And using website media, Facebook, Instagram, WhatsApp, and YouTube in promoting it. Third, the results of the promotion in selecting new outstanding students based online at MAN 2 Pamekasan got the best students as many as 222 students, and will be placed according to the interests of the students themselves. The 222 students were judged by the number of championships won and the level of championship they had.